Orthodontic camouflage as a treatment alternative for skeletal Class III - Monica Tirre de Souza ARAUJO; Luciana Rougemont SQUEFF (Dental Press Editora, 2021)
ABSTRACT Introduction: Skeletal Class III malocclusion is a deformity of complex treatment, with few intervention alternatives, which are further limited in nongrowing patients. In most cases, orthognathic surgery is the ideal treatment for adults, an option often refused by patients. Mild to moderate skeletal Class III malocclusions and acceptable facial esthetics can benefit from a course of treatment in which dental movements are used to compensate for the skeletal discrepancy. Objective: This study aimed to discuss orthodontic camouflage as an option for adult patients with Class III malocclusion, emphasizing its indications, implications and expected results.